Innovating War: Challenging Traditional Notions of Conflict and Scientific Development in the Cold War Era - Kamman, Jeremy; Long, Andrew; Hillard, Derek (My University, 2024)
I have been able to identify a relationship between innovation and conflict by comparing the Kondratieff Waves of Innovation with data on interstate conflicts from Our World in Data. Kondratieff Waves of Innovation are graphical representations of economic highs and lows, and they coincide with periods of technological development. -3rd Kondratieff Wave: 1880 - 1930 -4th Kondratieff Wave: 1930-1970 -5th Kondratieff Wave: 1970 – 2010